Review of pharmacological effects of imidazole derivatives - Daniya Serdaliyeva; Talgat Nurgozhin; Elmira Satbayeva; Malika Khayitova; Aida Seitaliyeva; Larisa Ananyeva (National Scientific Medical Center, 2022)
Imidazole derivatives are the perspective class of drugs with a broad spectrum of application in medicine. Imidazole is a nitrogen-containing heterocyclic ring; it has two equivalent forms; hydrogen atom may be located on any of two nitrogen atoms. Imidazole ring may interact with various cations and anions, as well as with biomolecules by different reactions; the presence of various groups in the nitrogenous heterocycle structure makes it possible to identify substances with a broad spectrum of pharmacological effects. They are very important for the production of new drugs and recently draw the special interest of scientists due to their properties in the chemistry and pharmacology. Introduction of highly active Imidazole has stimulated the significant achievements in the field of chemotherapeutic agents and plays the very important role in medicine. Therefore, the active search for highly active Imidazole compounds still continues. This article describes the antifungal and antibacterial effects identified in preclinical studies through a literature review. The purpose of this work is to review the principal effects of Imidazole published in the scientific literature in recent years.